Automated music therapy for anxiety and depression management in older people (AMITY) - Faizan Malik; White P.J.; Dey Indrakshi (E3S Web of Conferences)
The onset of old age is often accompanied by various physiological and mental changes, with anxiety and depression being prevalent mental health disorders that can exacerbate other medical conditions and significantly reduce life expectancy. Despite the growing need for effective treatment, the global shortage of mental health professionals, coupled with an ageing population and limited public awareness, has resulted in these disorders frequently going undiagnosed and untreated. Music therapy has emerged as a promising alternative for addressing the psychological, emotional, and cognitive needs of individuals, particularly older people. This paper proposes a novel approach for real-time monitoring of anxiety and depression symptoms using low-complexity body sensors. By employing automated, personalised music therapy based on the collected data, this system offers a scalable solution to enhance mental health care accessibility. It reduces the reliance on mental health professionals while providing tailored therapeutic interventions, thereby contributing to improved mental well-being and addressing the gap in mental health care services for the elderly population.